CAPGRAS SYNDROME AND ORGANIC BRAIN DYSFUNCTION - Bhatia, M.S. (Medknow Publications, 1996)
Capgras Syndrome was described in the late nineteenth century but its exact pathogenesis is still a source of controversy. Some believe its origin is due to psychodynamic factors whereas others have found the evidence of a generalized or localized brain lesion. We report three cases of Capgras Syndrome occurring in association with frontal lobe lesion.